Soft X-Ray Spectroscopy of Rare-Earth Elements in LHD Plasmas - Chihiro Suzuki; Fumihiro Koike; Izumi Murakami; Naoki Tamura; Shigeru Sudo; Gerry O’Sullivan (Atoms, 2019)
Soft X-ray spectra from high Z rare-earth (lanthanide) elements have been systematically observed in optically thin, high-temperature plasmas produced in the Large Helical Device (LHD), a facility for magnetically confined fusion research. It has been demonstrated that the discrete and quasicontinuum (UTA) spectral features from highly charged lanthanide ions are observed depending on the plasma temperature. The analyses of the measured spectra are ongoing by comparisons with theoretical calculations and/or previous experimental data available. The discrete spectra recorded in high-temperature conditions are dominated by individual lines of Ge- to Ni-like ions, while prominent peaks in the narrowed UTA spectra observed in low-temperature conditions are well explained by the transitions of Ag- to Rh-like ions.